A 34-Year-Old Obese Woman with Rash, Finger Swelling and Fever. (June 2017) - Huo, Na; Wu, Zhao; Dong, Xiaoqin; Feng, Li; Nong, Lin; Wang, He; Zhao, Hong
Summary: Disseminated tuberculosis first presenting as cutaneous lesion is uncommon and difficult to diagnose on account of its divers clinical forms. We present a 34-year-old obese woman with rash, finger swelling and fever. The patient was firstly manifested by fever and mass in palm and finger, gradually involving multisystems injury. She was diagnosed with disseminated tuberculosis in consideration of multiple system involvement, imaging characteristics, tuberculous granuloma in dermis and positive result of Mycobacterium culture. After two months of anti-tuberculosis treatment, fever and multisystems injury were controlled effectively, but skeletal and bone marrow involvement continued to progress, experiencing tuberculosis related acute hematopoietic stagnation. Continuing intensive therapy to one year, skeletal and hematological involvement improved and treatment was discontinued after two years. Follow-up to now with drug withdrawal for more than 1 year, the patient remains in remission.